The Growth Response of Oil Palm (Elaeis guineensis Jacq.) Seedlings in Pre Nursery to Treatment of Palm Oil Waste and N Fertilizer: Respon Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) Pada Pre Nursery Terhadap Perlakuan Limbah Kelapa Sawit dan Pupuk N - Asiah Wati; Mahdalena; Teguh Arif Saputra (Agrifarm : Jurnal Ilmu Pertanian, 2024)
This research aims to determine the best dose of Solid Palm Oil Waste and Nitrogen Fertilizer, as well as the interaction of the two treatments on the growth of oil palm seedlings in the Pre-nursery. This research was carried out at the experimental field of the Faculty of Agriculture, Widya Gama Mahakam University, Samarinda and was carried out for 3 months starting from April 2024 to June 2024. This research was arranged in a Factorial Randomized Group Design (RGD), overall there were 4 x 3 = 12 treatment combinations , and each treatment combination was repeated 3 times so that there were 36 experimental units. The first factor was 4 levels of Nitrogen Fertilizer, namely, N0= no treatment (control), N1= dose 8 g/polybag, N2= dose 10 g/polybag, N3= dose 12 g/polybag. The second factor is Solid Palm Oil Waste fertilizer consisting of 3 levels, namely S0= without treatment (control), S1= dose of 500 g/ 1 kg of polybag soil, S2= 550 g/ 1 kg of polybag soil. The results of the research on the treatment of solid oil palm waste had a significant effect on the treatment of stem diameter and number of leaves at 9 WAP and 12 WAP, nitrogen fertilizer had a significant effect on the treatment of plant height at 12 WAP, the interaction of solid oil palm waste fertilizer and nitrogen fertilizer had a significant effect on plant height at 12 WAP (U3S2), stem diameter 6 WAP (U1S0), 9 WAP (U1S1), 12 WAP (U3S1) and number of leaves at 12 MST (U2S1). Key word : berkelanjutan, efesiensi, zero waste